2009
DOI: 10.1007/s10879-008-9109-x
|View full text |Cite
|
Sign up to set email alerts
|

Using the MMPI-2 to Predict Symptom Reduction During Psychotherapy in a Sample of Community Outpatients

Abstract: In the present study, potential MMPI-2 predictors of psychotherapy outcome were examined in a community clinical sample of 51 patients seeking treatment at a university training clinic. Results indicated that particular MMPI-2 scales (L, F, Pd, Pa, Sc, Trt) were the most predictive of initial levels of patient distress, whereas three other clinical scales (Hs, D, Hy) were significantly associated with actual symptom reduction over time. The clinical implications of these data include the use of the MMPI-2 in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In terms of our Clinical scale hypotheses, we expected Pd and Ma—scales reflecting an externalizing and acting out coping style (see Groth-Marnat, 2003)—to be significantly lower for the Amish nonclinical group when compared to the United States normative sample and similar to the Amish outpatients due to prior personality research suggesting the Amish are more conforming, conscientious, shy, restrained, and accommodating than non-Amish (Wittmer, 1971). However, surprisingly, the Pd scale reached a T score of 50 for the Amish nonclinical group, comparable with the United States normative sample, and was significantly higher for the Amish outpatients, who scored similarly to non-Amish outpatient adults (see Castro, Gordon, Brown, Anestis, & Joiner, 2008; Michael et al, 2009). Yet, as predicted, the Ma scale was within the normal range for both Amish groups, slightly below the United States normative sample.…”
Section: Discussionsupporting
confidence: 53%
“…In terms of our Clinical scale hypotheses, we expected Pd and Ma—scales reflecting an externalizing and acting out coping style (see Groth-Marnat, 2003)—to be significantly lower for the Amish nonclinical group when compared to the United States normative sample and similar to the Amish outpatients due to prior personality research suggesting the Amish are more conforming, conscientious, shy, restrained, and accommodating than non-Amish (Wittmer, 1971). However, surprisingly, the Pd scale reached a T score of 50 for the Amish nonclinical group, comparable with the United States normative sample, and was significantly higher for the Amish outpatients, who scored similarly to non-Amish outpatient adults (see Castro, Gordon, Brown, Anestis, & Joiner, 2008; Michael et al, 2009). Yet, as predicted, the Ma scale was within the normal range for both Amish groups, slightly below the United States normative sample.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, the study conducted by Michael, Furr, Masters, Collett, Spielmans, Ritter, Veeder, Treiber and Cullum (2009) involved the combined administration of both the MMPI-2 questionnaire and the OQ-45 scale in a clinical sample. In this way, it was possible to identify potential MMPI-2 predictors of psychotherapy outcomes.…”
Section: Introduction and Previous Empirical Studymentioning
confidence: 99%
“…Tendencies to overreport pathology on the MMPI‐2 have been associated with poorer treatment outcomes (Hyer et al, ; Perconte & Griger, ). An MMPI‐2 profile with low scores on the Lie (L) scale or elevated Infrequency (F) scale scores may be suggestive of overreporting, and this configuration has been found to predict high levels of initial distress on other self‐report measures (Michael et al, ). The MMPI‐2 also has several clinical scales that are pertinent to PTSD and have been found to be related to treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The MMPI‐2 also has several clinical scales that are pertinent to PTSD and have been found to be related to treatment outcomes. For example, individuals with elevations on scales associated with antisocial characteristics, depression, and hypochondriasis/somatization have been shown to demonstrate less improvement during treatment than others without elevations on these scales (Forbes et al, ; Michael et al, ). However, a recent study using secondary data from a CPT trial examined the interaction between personality disorders and treatment outcome for female rape survivors and reported that reductions in PTSD symptoms were associated with change in Antisocial Personality Disorder (ASPD) symptoms at follow‐up and that decreases in ASPD symptoms predicted change in PTSD symptoms at follow‐up (Bovin, Wolf, & Resick, ).…”
Section: Introductionmentioning
confidence: 99%